Visual Status of Professional Drivers in Eastern Nepal (Purbanchal University Health Journal, 2022)
Introduction: Vision is the main sensory input to the brain for driving. Other aspects of visual function like color vision, contrast sensitivity, visual field, night vision, etc and not merely visual acuity should be evaluated before issuing a driving license.Objective: The objective of the study was to determine the visual status of the professional drivers in Eastern Nepal.Method: A cross-sectional descriptive study was carried out to assess visual functions like visual acuity, color vision, contrast sensitivity and visual field in 172 drivers who drove long haul commercial passenger vehicles.Result: More than half of the drivers (51.2%) belonged to the age group 31-40 years. On evaluation of distance Visual Acuity, only one person had uncorrected visual acuity ≤ 6/18 in the better eye. Color vision anomaly was present in 2 persons (1.2%).Conclusion: Visual status of the professional drivers in Eastern Nepal was normal on assessment of the different visual functions.